Transformasi Intelektual Islam: dari Bayt Al-Hikmah ke Era Digitalisasi Pendidikan - Hamid, Ahmad Masthur; subhi, Muhamad Rifa’i; Anekasari, Rahmi (Jurnal Tinta, 2025)
This article examines the intellectual transformation of Islamic education by exploring the legacy of Bayt al-Hikmah during the Abbasid Caliphate and its relevance to the current era of educational digitalization. Employing a qualitative historical-conceptual approach through library research, the study finds that Bayt al-Hikmah served as a pioneering model of Islamic scholarship integrative, multidisciplinary, and open to diverse sources of knowledge across civilizations. Its curriculum emphasized critical thinking, practical scientific engagement, moral development, and intercultural academic dialogue. These foundational values remain deeply relevant in addressing the challenges of 21st century Islamic education. In the digital era, technology can be positioned not merely as a tool but as a medium to revive and modernize the intellectual spirit of classical Islam. By adopting the principles of Bayt al-Hikmah, digital education can promote inclusive knowledge exchange, character formation, and cross-institutional collaboration. Thus, digital transformation in Islamic education should not only aim at technological advancement but also at restoring the rich intellectual tradition that once shaped Islamic civilization.